PENGEMBANGAN PENUNTUN PRAKTIKUM KIMIA BERBASIS PENDEKATAN SAINTIFIK PADA MATERI LAJU REAKSI UNTUK SISWA KELAS XI IPA DI SMA ADISUCIPTO PONTIANAK - Rani Aprianti; Tuti Kurniati; Rizmahardian Azhari Kurniawan (Universitas Muhammadiyah Pontianak, 2018)
Low students’ understanding of reaction rate factors had occurred in grade XI of SMA Adi Sucipto Pontianak as a result of lack of learning resources. Therefore, this study aimed to develop an experiment guidebook based on a scientific approach to assist students on comprehending factors influencing reaction rate. Modified 4D Thiagarajan’s model of Research and Development (R&D) was carried out, in which the guidebook was evaluated regarding its feasibility including validity, effectiveness, and practicality. The validity value judged byexperts of mediawas 87.64% (very valid). In addition, the practicality level measured by responses from both teacher and students were 100% (very practical) and 98.14% (very practical), respectively. The use of the guidebook in classroom was effectively improved students’ learning outcome as the N-gain value was 0.89 (very high). As a conclusion, the resulted experiment guidebook based on a scientific approach was feasible to be used as a learning resources on reaction rate subject in grade XI of SMA Adisucipto Pontianak.Keywords: Chemical Practic Guides, Scientific Approach.